The Effect of Liquidity on Profitability with Leverage as Mediation in Manufacturing Companies Food and Beverage Subsectors Registered in Indonesia Stock Exchange 2022-2023 - Baiq Emi Supiana; I Nyoman Nugraha Ardana Putra (LP2M IAIN Palopo, 2026)
The manufacturing sector, particularly the food and beverage subsector, contributed 6.61% of Indonesia's GDP in 2023, but faces a liquidity-profitability imbalance amid post-pandemic challenges. This study aims to analyze the effect of liquidity on profitability with leverage as a mediating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2023 period. Using a quantitative causal associative approach with an explanatory research design and path analysis, the population included 83 companies, with a purposive sample of 34 companies resulting in 68 observations. Variables measured as the current ratio (CR) for liquidity, debt-to-equity ratio (DER) for leverage, and return on assets (ROA) for profitability were analyzed using EViews 13, including multiple regression, t-test, F-test, and Sobel test. The results showed no significant direct effect of liquidity on profitability (p=0.1432) or mediation by leverage (Sobel Z=0.281, p>0.05), with low explanatory power (Adjusted R²=0.004466). In conclusion, external factors dominate the dynamics of profitability, so efficient asset management is required rather than excess liquidity.